STOCK SIZE IN INDIVIDUAL FARMS ACCORDING TO SELECTED CRITERIA - Wasilewski, Mirosław (Acta Scientiarum Polonorum. Oeconomia, 2003)
In the paper, the analysis of both volume and value of stocks of commodities produced by individual farms was presented. The results show that in the case of cereals, the difference in stock volume between the group of the smallest farms and the group the largest farms by area size was slight. It suggests the comparable stock managing in considered groups of farms. Positive relation between total cereal stocks and farm income per 1 ha UAA was noted. The most important difference between those types of farms was observed in the case of stocks of silage. Total stock value in group of farms which hold the best soils was over twice higher than in farms with the worst soils. Moreover, in all types of farms the equal stock values of agricultural products were assessed, therefore the stocks in value terms do not depend on the type of farm.